Dynamic and Interesting Events: The Nineteenth-Century Māori Elections - Warbrick, Paerau (New Zealand Journal of History, 2019)
The article discusses the history of the political participation of the Maori people of New Zealand in the 19th century which started with the creation of the Maori seats of Parliament under the Maori Representation Act 1867 (MRA). Topics discussed include the incorporation of MRA into the Electoral Act of 1893, the history of their voting rights, practices and election participation, and the issue of giving fair representation to Maori in the House of Parliament in 1862.
Keywords: government relations; history; māori seats; voting

Screaming from the shadows: Māori views on the treaty claims settlement process - McDowell, Tiopira (Te Pouhere Kōrero Journal, 1999)
Keywords: history; periodicals; treaty claims; waitangi tribunal